1999
DOI: 10.1128/aem.65.8.3279-3286.1999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mimotope Peptides Which Bind to the Mycotoxin Deoxynivalenol-Specific Monoclonal Antibody

Abstract: Monoclonal antibody 6F5 (mAb 6F5), which recognizes the mycotoxin deoxynivalenol (DON) (vomitoxin), was used to select for peptides that mimic the mycotoxin by employing a library of filamentous phages that have random 7-mer peptides on their surfaces. Two phage clones selected from the random peptide phage-displayed library coded for the amino acid sequences SWGPFPF and SWGPLPF. These clones were designated DONPEP.2 and DONPEP.12, respectively. The results of a competitive enzyme-linked immunosorbent assay (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 44 publications
0
41
2
Order By: Relevance
“…The present results show that a¯atoxin MAbs select several approximately equally strongly binding peptides. This contrasts with the results obtained by Yuan et al (1999) with mimotopes isolated from an unconstrained library for MAbs speci®c to the toxin deoxynivalenol. Possibly, the mimotope these authors obtained is a much stronger binder than any others present in the library used for the panning.…”
Section: Mimotope 24±4á1contrasting
confidence: 92%
See 1 more Smart Citation
“…The present results show that a¯atoxin MAbs select several approximately equally strongly binding peptides. This contrasts with the results obtained by Yuan et al (1999) with mimotopes isolated from an unconstrained library for MAbs speci®c to the toxin deoxynivalenol. Possibly, the mimotope these authors obtained is a much stronger binder than any others present in the library used for the panning.…”
Section: Mimotope 24±4á1contrasting
confidence: 92%
“…There are few reports of the selection of mimotopes for antibodies to non-proteinaceous chemicals, other than biotin (Weber et al 1992) and carbohydrates (Hoess et al 1993). Recently, Yuan et al (1999) showed that it was possible to obtain mimotopes to MAbs raised against the mycotoxin deoxynivelenol. The mimotopes obtained were essentially of a single amino acid sequence.…”
Section: Introductionmentioning
confidence: 99%
“…There are growing evidences that indicate that deoxynivalenol can enhance the virulence of plant-pathogenic Fusarium species on plant hosts (Proctor et al, 1995;Yuan et al, 1999), and it causes many diseases in plants, including head and seedling blight of small grains, such as wheat and rye, ear and stalk rot of maize, and seedling blight and root rot in a number of other plant species, including beans, clover and tomato (Eriksen et al, 2003;Schneider et al, 2004). Therefore, more rapid and sensitive methods towards deoxynivalenol detection should be established, and these may lead to prevention of plant and animal diseases associated with this mycotoxin.…”
Section: Discussionmentioning
confidence: 99%
“…Deoxynivalenol (DON, vomitoxin), a trichothecene mycotoxin, is mainly produced by the fungus Gibberella zeae (Schwein) Petch (anamorph, Fusarium graminearum Schwabe), which is the causing agent of wheat and barley scab, corn ear rot diseases (Yuan et al, 1999;Fox et al, 2004). Biochemically, deoxynivalenol is an inhibitor of protein synthesis and has hemolytic activity, causing apoptosis (cytotoxicity) and immunotoxicity to eukaryotic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the commonality of amino acid residues of the mAb involved in interactions with gibberellin A 4 (GA 4 ) and peptide SD, we concluded that peptide SD is bound to the antigen-binding site of mAb 4-B8(8) ⁄ E9 as a GA 4 mimic, confirming evidence for the existence of peptide mimics even for hydrophobic ligands. exception of the water-soluble ligands biotin [4] and deoxynivalenol (DON) [5]. If peptidyl mimics for hydrophobic ligands become generally available, they could work as ideal immunogens to create antibodies that possess high binding activities to various organic compounds such as plant hormones.…”
Section: Notementioning
confidence: 99%